2012
DOI: 10.1002/jae.2289
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Are Unemployment Benefit Sanctions? Looking Beyond Unemployment Exit

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(84 citation statements)
references
References 29 publications
0
78
0
6
Order By: Relevance
“…First, we follow Arni et al (2009) by modeling the post-treatment wage explicitly. However, contrary to them, we specify a log-normal distribution for the post-unemployment wage, that is,…”
Section: Modeling Post-unemployment Outcomesmentioning
confidence: 99%
“…First, we follow Arni et al (2009) by modeling the post-treatment wage explicitly. However, contrary to them, we specify a log-normal distribution for the post-unemployment wage, that is,…”
Section: Modeling Post-unemployment Outcomesmentioning
confidence: 99%
“…The study concludes that the net effect of benefit sanctions is negative in macroeconomic terms -because equilibrium unemployment is not affected (i.e. reduced unemployment duration and reduced employment duration cancel each other out) and in microeconomic termsbecause individuals are forced into unstable jobs and face a reduction in their life-time income (Arni et al, 2013). Another study yields similar findings about persistent sanction effects on subsequent job quality (Van den Berg and Vikström, 2009: 45).…”
Section: Exit To Precarious Employmentmentioning
confidence: 60%
“…Arni et al found that 12.5 per cent of the sample exited to non-employment, with 'a remarkable rise' in the rate of exit to non-employment -99 per cent in response to a sanction announcement. They also found that an enforced sanction 'results in an additional increment' of 67 per cent to the exit to non-employment rate (Arni et al, 2013(Arni et al, : 1165. In some cases, people become unregistered as unemployed while continuing to look for work (Arni et al, 2013(Arni et al, : 1166.…”
Section: Exit To Non-employmentmentioning
confidence: 99%
See 2 more Smart Citations